Why ABC (Activity-Based Costing)? / Razali Daud - Daud, Razali (Universiti Teknologi MARA Cawangan Pahang, 2001)
Activity-Based Costing (ABC) system is a fairly new management innovation. Basically ABC system improves the accuracy of product and service costing which is very important in today's business environment. Indirect costs are becoming more prominent with today's business where the emphasis is more on capital and technology intensive mode of operation. With intense competition, the need for the indirect cost to allocated accurately is even greater. Traditional costing system which emphasize on volume based allocation system is simply not adequate to handle the task of allocating indirect costs accurately to product and services. Empirical evidences found through out the late 90's strongly suggest there are benefits to companies from adopting the ABC system.